Protecting Children and Adults from Abuse after Savile : What Organisations and Institutions Need to Do. - McAlinden, Anne Marie (Jessica Kingsley Publishers, 2018)
The high profile reporting of child sexual abuse carried out by Jimmy Savile over decades has had far reaching-consequences, raising public awareness and concern, yet we continue to uncover new cases of institutional abuse which have been taking place under the radar for years.This book distils the learning from 80+ public inquiries relating to Savile as well as related cases of institutional abuse and analyses the key findings. It examines what we now know about offending within organisations and institutions, and how organisational failures can enable abusers. Each chapter also outlines solutions, offering perspectives for individuals and organisations on what practical action they can take to minimise risk in the settings in which they work.The book includes chapters specifically dedicated to the NHS, sports organisations and schools, and is necessary reading for professionals with responsibility for safeguarding in any setting.